Keanekaragaman Makrozoobenthos Pada Ekosistem Mangrove Rehabilitasi Dan Mangrove Alami Di Ekowisata Nelayan Wanasari Tuban, Bali - Ni Putu Laras Berliana Cahayani; Sang Ayu Md Putri Suryani; I Made Kawan (Fakultas Pertanian, Universitas Warmadewa, 2022)
The research was aims to determine the biodiversity of macrozoobenthos in mangrove rehabilitation and natural mangrove ecosystem in Wanasari Fisherman Ecotourism Tuban, Bali. This research was conducted in May until June 2021 in Wanasari Fisherman Ecotourism area Tuban, Bali. This research is an exploratory descriptive study using quadran transect method and conducted analysis of species diversity index (H’), species uniformity (E) and type dominance (D) in mangrove rehabilitation and natural mangrove ecosystem. Based on research was founded 6 species macrozoobenthos consisting 5 class Gastropoda and 1 class Crustacea which is dominance by class Gastropoda while in natural mangrove there are 13 species of macrozoobenthos consisting 7 class Gastropoda, 2 class Crustacea and 4 class Bivalvia which dominance by class Gastropoda. The conclusion obtained from the result of the research that biodiversity macrozoobenthos within 2 ecosystem in mangrove rehabilitation and natural mangrove ecosystem in the same be classified as low category.